The Assessment of Services Quality in the Central Library of Science & Culture University as viewed by users - Ahmad Reza Ahmadimirgaed; Reza Maleki; Esmat Momeni (بازیابی دانش و نظام‌های معنایی, 2015)
Purpose: we aimed to assess the level of service quality in the central library science and culture using standard tools LibQual, examining the differences between users' expectations and the level of services received determined by the need to improve the service components and to prioritize the elements of a list view of the library. This study assessed the quality of library services based on users' expectations on three levels: minimum, maximum estimated and analyzed. Methodology: The study population consisted of 2250 members of the Central Library, Science and Culture, including PhD students, graduate students, undergraduate students, faculty fellow members and employees. Given the sheer size and distribution of the study population, random stratified sampling was used. The sample of study includes 328 students. Findings: Our findings indicated that the influence of the level of service received, the Central Library of Science and Culture, with a mean (33/7) is more than the other dimensions. But the library as a place was not able to meet users' needs and their expectations and with a mean (58/3) to have the lowest level of service received. According to users' perspective, information control (07/60%), service work components (21/26%) and the component library as a place (72/13 percent) were the main important component, respectively. Conclusion: After testing the hypotheses, it was determined that in LibQual components there was a significant relationship between the users' highest and lowest expectations and the level service received. Also there was a significant difference among perspectives of PhD students, graduate students, undergraduate students, faculty fellow members and employees in the lowest expectations", "the highest expectations" and "received services". Finally, with the results obtained in the field and to improve the level of service quality in academic libraries, solutions and recommendations were presented.